(untitled) - Durant Will (New York, 1961)
The book presents a brillant and concise account of the lives and ideas of the great philosophers - Plato, Aristote, Bacon, Spinoza, Voltaire, Kant, Schopenhauer, Spencer, Nietzsche, Bergson, Croce, Russell, Sntayana, james and Dewey
Keywords: philosophy